Fossil freshwater fishes and the biogeography of northern South America - Chaparro, Gustavo Adolfo Ballen (2020)
Fossil vertebrates have been used in the literature as a source of information on past paleogeographic settings in the Neotropics, although fishes in special have been less studied despite availability in collections and in the field. Appendicular fossil remains are one of the most common occurrences of fossil catfishes and tend to be locally abundant in well-known faunas of Cenozoic age in South America; however, the comparative anatomy of these anatomical complexes has been poorly studied, with a complex and confusing anatomical terminology where each published reference ignores previous terms provided and thus creates a number of different synonyms for the same osteological feature. It was carried out a thorough literature review along with direct examination of extant representatives of the order Siluriformes in order to provide a standardized anatomical terminology for the dorsal- and pectoral-fin spines in the order. Three continental vertebrate faunas have been found in northern Colombia, in an area that is currently separated from the Amazon-Orinoco drainages by the Andes of the Cordillera Oriental in Colombia and the Merida Andes in Venezuela. Fossil freshwater fishes from the middle Miocene Castilletes formation are herein described along with their bearing on different topics ranging from taxonomy and comparative anatomy to paleogeographic and paleoenvironmental reconstructions; this fossil assemblage conforms to previous models of paleodrainage connections between cis- and trans-Andean areas in the literature. Two faunas of Pliocene age from the Sincelejo and Ware formations were studied using a similar approach to that of the fossil assemblage of the Castilletes formation. The assemblages of Pliocene age imply the persistence of a hydric connection between drainages now separated by the Andes, that is, they extend towards the present the same pattern recovered in the assemblage of middle Miocene age and are against the classical tectonic models of the northern Andes that suggest a loss in drainage connectivity about 11-13 Ma. A set of quantitative methods for inferring the time of separation between two biogeographic areas using data from divergence time estimation are herein proposed and discussed as promising methods for statistical estimation in biogeography. Although primarily designed with vicariant patterns in mind, these methods are extensible enough as to be applicable to any kind of event occurring in geologic time that leaves traces in divergence time estimation studies. The different methods mostly suggest a separation interval of 2-5.8 Ma, consistent with the information from the fossil assemblages that imply a connection persisting to about the same interval, therefore, the fossil faunas of the Sincelejo and Ware formations would be the last evidence of drainage connections across the Andes. Within this temporal framework, a number of biodiversity patterns such as faunal composition, endemism rates and spatial patterns, and the timing of generation of biodiversity at regional to continental scale should be reassessed in light of the results herein provided.